Semi-surrogate modelling of droplets evaporation process via XGBoost integrated CFD simulations - Yan, Yihuan; Li, Xueren; Sun, Weijie; Fang, Xiang; He, Fajiang; Tu, Jiyuan (The Science of the total environment, 2023)
The applications of machine learning (ML) based approach are emerging as possible tools to accelerate CFD simulations. This study proposed a semi-surrogate model for CFD with integration of the cutting-edge ML algorithm, eXtreme Gradient Boosting (XGB), which enlightened a possible pathway to effectively and efficiently solve and predict those costly but highly repetitive fluid dynamics-related problems. Droplet evaporation, a complex but essential phenomenon in respiratory droplets transport, was studied as the practical case using the proposed model. Droplets evaporation and dynamic size distributions were firstly tracked under various combinations of indoor humidity and temperature using traditional Eulerian-Lagrangian CFD framework, followed by generating several datasets for XGB training. The trained XGB was then used to interpret the evaporated droplets size over time under new combinations of indoor conditions. Outcomes revealed that well-trained XGB-base semi-surrogate model was capable of interpreting complex non-linear relationships between droplets dynamic parameters (diameter and time) and indoor parameters (humidity and temperature). For each specific parameter, the predictive error of well-trained XGB could retain below 5 % and its prediction speed was found nearly 1 million times faster than that of new CFD simulations. Successful applications of XGB in conjunction with CFD demonstrated its great potential on providing rapid and more efficient predictions of complex, costly and repetitive fluid dynamics-related phenomenons (e.g. droplets evaporation). Also, the XGB predicted droplets evaporation data from this study could be further applied as initial conditions into new simulations via the User-defined function (UDF). [Display omitted] •A semi-surrogate model is developed via integrating XGBoost and CFD approach.•Droplet dynamic characteristic is properly predicted using the semisurrogate model.•Well-trained model is able to have less than 5 % errors in predicting specific data.•Using XGBoost on predicting droplet diameters is 1 million faster than using CFD.•Semi-surrogate model enables a cost-effective prediction of large-scale problems.